Comparative Study of High Temperature Oxidation of Mild Steel in Hydrogen, Sulphur, and Carbon Dioxide Atmospheres - Obot, Obotowo W.; Chibuike, Chinda Believe (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2018)
Fabricated materials made from mild steel tend to corrode when exposed to the atmosphere overtime, and often result mostly in the complete failure of materials while in service. This research aimed at establishing the relationship between oxidation of mild steel and temperature; the comparison of oxidation of mild steel at high temperature in different atmospheres, and the calculation of the rate of oxidation of mild steel at elevated temperatures. Mild steel finds application in weldable boiler tubes and in weldable turbines requiring very high temperature for its operation, hence this research was carried out at a maximum temperature of 1000 OC and samples were pre-treated in the different atmospheres for 96 hours intervals for 480 hours. The mild steel samples used in this research were labelled samples 1 and 2 and composed 0.19875 %C and 0.19220 %C, respectively. The atmospheres in which the experiment was carried out included hydrogen, sulphur and carbon dioxide. The result of the experiment showed that the rate of oxidation of mild steel followed parabolic relationship, also the rates were different in the different atmospheres and the highest rate occurred in carbon dioxide.